2018
DOI: 10.1093/nar/gky1208
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of intracellular stress-induced tRNA trafficking

Abstract: Stress is known to induce retrograde tRNA translocation from the cytoplasm to the nucleus but translocation kinetics and tRNA-spatial distribution have not been characterized previously. We microinject fluorescently-labeled tRNA into living cells and use confocal microscopy to image tRNA spatial distribution in single cells at various levels of starvation and to determine translocation rate constants. Retrograde tRNA translocation occurs reversibly, within minutes after nutrition depletion of the extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Many stress conditions are known to result in the accumulation of tRNAs in the nucleus, such as amino acid deprivation ( 18 ). A recent study examining the kinetics of tRNA import and re-export upon nutrient deprivation in mouse embryonic fibroblasts microinjected with fluorescently labeled tRNA, found that tRNAs accumulate in the nucleus upon nutrient deprivation and the rate constants of tRNA import and re-export both decrease as nutrient levels decrease ( 43 ). However, the rate of re-export decreases to a greater extent than the rate of import, accounting for the nuclear accumulation of tRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Many stress conditions are known to result in the accumulation of tRNAs in the nucleus, such as amino acid deprivation ( 18 ). A recent study examining the kinetics of tRNA import and re-export upon nutrient deprivation in mouse embryonic fibroblasts microinjected with fluorescently labeled tRNA, found that tRNAs accumulate in the nucleus upon nutrient deprivation and the rate constants of tRNA import and re-export both decrease as nutrient levels decrease ( 43 ). However, the rate of re-export decreases to a greater extent than the rate of import, accounting for the nuclear accumulation of tRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Cytoplasmic tRNAs rapidly translocate into the nucleus under a number of stress conditions, including nutrient starvation (Shaheen and Hopper, 2005;Takano et al, 2005;Hurto et al, 2007;Shaheen et al, 2007;Whitney et al, 2007;Dhakal et al, 2019), heat shock (Miyagawa et al, 2012;Watanabe et al, 2013), viral infection (Zaitseva et al, 2006), and oxidative stress (Schwenzer et al, 2019). This translocation not only directly depletes tRNAs from protein synthesis but also modulates stress response by activation of the GCN2 kinase (Castilho et al, 2014).…”
Section: Trnas Modulate Global Gene Expressionmentioning
confidence: 99%
“…tRNAs move dynamically between the nucleus and the cytoplasm in yeast, protozoa, and vertebrate cells (Shaheen and Hopper, 2005; Takano et al., 2005; Shaheen et al., 2007; Huynh et al., 2010; Barhoom et al., 2011; Ohira and Suzuki, 2011; Watanabe et al., 2013; Dhakal et al., 2018; Kessler et al., 2018). Even though only a subset of eukaryotic tRNA-encoding genes contains introns, we focus on this category of tRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Employing nuclear import assays with permeabilized HeLa cells, the Fassati group demonstrated that tRNA nuclear import occurs in vertebrate cells and their studies also showed that tRNA retrograde traffic provides one mechanism by which the retrotranscribed HIV genome can access the nuclear interior in nondividing cells (Zaitseva et al., 2006). Subsequent RNA FISH studies in protozoa, brine shrimp, and vertebrate cells in culture, and, most recently, tagged-tRNAs injected into vertebrate live cells, demonstrate widespread conservation of nuclear import of cytoplasmic tRNAs, especially in response to nutrient and/or heat stress [(Huynh et al., 2010; Barhoom et al., 2011; Miyagawa et al., 2012; Watanabe et al., 2013; Chen et al., 2016; Dhakal et al., 2018) Review: (Huang and Hopper, 2016)].…”
Section: Introductionmentioning
confidence: 99%